KESANTUNAN TUTURAN TOKOH UTAMA DALAM DRAMA GREAT TEACHER ONIZUKA 2012 - Ardianti Ardianti; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research discusses about politeness scale in drama Great Teacher Onizuka 2012. The purpose of this research is to find out how the politeness scale of the main character's speech in that drama. The research method used is a qualitative descriptive method. The data is obtained by listening to the conversations spoken by the main character. Then the speech which has a politeness scale is recorded and marked. The results of this study indicate that in drama Great Teacher Onizuka 2012, the main character uses five kinds of Leech’s politeness scales, cost-benefit scale, optionality scale, indirectness scale, authority scale and social distance scale. On the five scales, the scale that often appears is indirectness scale and the scale that appears the least is authority scale.Key Words: Leech’s politeness scale, speech, Great Teacher Onizuka, Japanese Drama